ON PARA-LINDELÖF AND SEMIPARA-LINDELÖF BITOPOLOGICAL SPACES - Al-Faham, Afifa Yousif Jafar; Al- Awadi, Heyam Kh (Al-Nahrain Journal of Science, 2009)
We define a paraLindelöf bitopological space and semiparLindelöf bitopological space and we find some properties of these concepts and give the relation between these concepts.